The Use Of "The Flash" Movie Scenes To Teach Idioms For Tenth Grade Students Of SMK Katolik St. Mikael Surakarta - Singgih Prastawa; Ribut Agung Sutrisno (Jurnal Intelek Insan Cendikia, 2026)
This paper examines the effectiveness of using scenes from the movie "The Flash" to teach idioms to vocational school students. Idioms are often difficult for learners to grasp due to their non-literal meanings. By incorporating scenes from a popular movie, educators can provide contextual and visual support that enhances comprehension and retention. This study reviews relevant literature, discusses the benefits and challenges, and proposes practical strategies for implementation. This paper provides a comprehensive overview of using "The Flash" movie scenes to teach idioms in vocational schools, combining theoretical insights with practical applications to enhance the learning experience.